The Effectiveness of Adobe Flash CS5 Learning Media on Explanatory Text Material in Public Senior High School 1 Padang Bolak - Riky Gunawan Siregar; Mara Untung; M. Oky Fardian Gafari (BIRCU, 2019)
The aims of this study is to find out the effectiveness of Adobe Flash CS5 Learning Media. This research was carried out in Public Senior High School 1 Padang, Bolak 2018/2019 Academic Year. Implementation of treatment (treatment) in the form of learning activities that are tailored to the education calendar. The population of this research and development are students of Public Senior High School 1 Padang Bolak. The result of this study The effectiveness of student learning outcomes tests got an average score of 81% with the criteria of